2022
DOI: 10.3389/ijph.2022.1604973
|View full text |Cite
|
Sign up to set email alerts
|

Who Said What: A Multi-Country Content Analysis of European Health Organisations’ COVID-19 Social Media Communication

Abstract: Objectives: As a risk communication tool, social media was mobilised at an unprecedented level during the COVID-19 pandemic. This study examined health authorities’ risk communication on social media in response to the pandemic in 2020.Methods: We analysed 1,633 COVID-19-related posts from 15 social media accounts managed by official health authorities in Germany, Norway, Sweden, Switzerland, and the United Kingdom.Results: The rate at which the authorities posted about COVID-19 on social media fluctuated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In line with previous findings (e.g., Kompani et al, 2022), this study indicates that Twitter communication is, in some cases, used for different purposes than other social media platforms. It suggests that health agencies used their tweets to disseminate general information on COVID-19 virus characteristics and on the re-opening of business activities after the lockdown.…”
Section: Othersupporting
confidence: 92%
See 2 more Smart Citations
“…In line with previous findings (e.g., Kompani et al, 2022), this study indicates that Twitter communication is, in some cases, used for different purposes than other social media platforms. It suggests that health agencies used their tweets to disseminate general information on COVID-19 virus characteristics and on the re-opening of business activities after the lockdown.…”
Section: Othersupporting
confidence: 92%
“…However, after the rolling of COVID-19 vaccination began, many posts were dedicated to this theme. Kompani et al's (2022) study demonstrated that messages' contents during a pandemic can vary depending on the stages of the pandemic.…”
Section: Public Discourse On Public Health Crisesmentioning
confidence: 91%
See 1 more Smart Citation
“…After a quick response to the emergency, with the promulgation of safety regulations internally and across borders, sanitary protocolsfrom lockdown to using hand sanitisers and wearing a face mask on public transport and in storeswere adopted to mitigate the impact on overloaded healthcare systems. Besides the implementation of safety measures to reduce health risks and fines in case of violations, efforts were made by local health authorities to elaborate and share warnings, instructions and advice all-round in an accessible way (Jucks and Hendriks 2021; Smith and Kabele 2021; Kompani et al 2022). However, institutional communication often stumbled against the perceived lack of clarity or unexpected emotional reactions from citizens.…”
Section: Recovery and Resiliencementioning
confidence: 99%
“…There are now many new opportunities for users to gather information on health-related topics on social media platforms. There has been an influx of social media users following health authorities' social media pages, and this has presented a good opportunity for health communication campaigns (Kompani et al, 2022). Numerous studies have highlighted the success and potential of social media platforms for health communication campaigns.…”
Section: Twitter As a Social Media Platformmentioning
confidence: 99%